OIL PRICES AND INFLATION IN NIGERIA: AN EMPIRICAL ANALYSIS OF NONLINEAR RESPONSES TO OIL PRICE CHANGES - IHUGBA, OKEZIE A; ADEFABI, RASAK A (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the nonlinear relationship between oil prices and inflation in Nigeria from 1981 to 2024, using the Nonlinear Autoregressive Distributed Lag (NARDL) model. It investigates the asymmetric effects of positive and negative oil price shocks on inflation while accounting for factors such as reserves, money supply, GDP growth, and monetary policy rates. The results show that past inflation significantly impacts current inflation, with a 1% increase in past inflation leading to a 0.63% rise in current inflation. Positive oil price shocks initially have short-term negative effects on inflation but create a significant positive relationship in the long run, particularly with lagged periods. Conversely, negative oil price shocks initially raise inflation, but later periods show a deflationary impact. Changes in total reserves significantly reduce inflation, and past money supply growth notably influences inflation dynamics. The Broad Money Supply (LM2) initially reduces inflation but later raises it, with a negative effect at -66.8034 and a positive effect at 40.1919. GDP growth shows no immediate impact on inflation but has a positive effect after three periods. The Monetary Policy Rate (MPR) has a varying effect, with a positive relationship suggesting that higher interest rates initially increase inflation. The error correction term reveals that inflation adjusts quickly to its long-run equilibrium. Based on these findings, the study recommends targeted monetary policies, strategic reserve management, and economic diversification to mitigate the impact of oil price fluctuations on inflation